Mesoscale modelling of optical turbulence in the atmosphere: the need for ultrahigh vertical grid resolution. Issue 2 (13th July 2020) - Basu, S; Osborn, J; He, P; DeMarco, A W
ABSTRACT: The high-fidelity modelling of optical turbulence is critical to the design and operation of a new class of emerging highly sophisticated astronomical telescopes and adaptive optics instrumentation. In this study, we perform retrospective simulations of optical turbulence over the Hawaiian islands using a mesoscale model. The simulated results are validated against thermosonde data. We focus on turbulence in the free atmosphere, above the atmospheric boundary layer. The free atmosphere is particularly important for adaptive optics performance and for sky coverage calculations and hence has significant impact on performance optimization and scheduling of observations. We demonstrate that a vertical grid spacing of 100 m or finer is needed to faithfully capture the intrinsic variabilities of observed clear air turbulence. This is a particularly timely study because the next generation of extremely large telescopes are currently under construction and their associated suite of instruments are in the design phase. Knowledge of the expected accuracy of optical turbulence simulations and real-time forecasts will enable the design teams to (i) test and develop instrument designs and (ii) formulate operational procedure.